مساهمة النخبة الجزائرية فى كتابة التاريخ الوطنى من خلال " مجلة الأصالة " - رحماني، فاطمة الزهراء; دراج، محمد (جامعة الجلفة, 2018)
This study deals with the contribution of the Algerian elite in the codification and rewriting of the national history and its identify the historical studies that serve the heritage and history of Algeria from ancient times to the modern age and contemporary times. With a focus on the Algerian literature contained in the journal El Assala, which is a free platform expressed by this elite showed it srefusing position to the accusations and suspicions that the colonization writings claimed against the history of Algeria, as well as contain multiple articles and varied formed a circle of knowledge that combines the historical and philosophical and what is Linguistic and artistic.
تعالج هذه الدراسة إسهامات النخبة الجزائرية في تدوين وإعادة كتابة التاريخ الوطني، والتعرف على ما قدمته من دراسات تاريخية تخدم تراث وتاريخ الجزائر من العصور القديمة إلى العصور الحديثة والمعاصرة. مع التركيز على الكتابات الجزائرية التي تضمنتها مجلة الأصالة، التي تعد منبراً حراً أبدت من عليه هذه النخبة موقفها الرافض للاتهامات والشبهات التي ادعتها الكتابات الاستعمارية في حق تاريخ الجزائر، فضلاً عن احتوائها على مقالات متعددة متنوعة شكلت دائرة معارف جمعت بين ما هو تاريخي وفلسفي وبين ما هو لغوي وفني.
Keywords: النخية الجزائرية -- مجلة الأصالة -- التاريخ الجزائرى -- الدراسات التاريخية -- الشبهات الاستعمارية